2018
DOI: 10.1177/1526602818783506
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function Salvage After Delayed Endovascular Revascularization of Acute Renal Artery Occlusion in Patients With Fenestrated-Branched Endovascular Aneurysm Repair or Visceral Debranching

Abstract: Renal function can be salvaged by delayed revascularization for RAO with prolonged renal ischemia. The endovascular approach with aspiration thrombectomy, local lysis, and stent-graft relining is a feasible technique for revascularization after RAO in patients with fenestrated-branched EVAR or open visceral debranching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…They found that renal function can be salvaged, even if the revascularization procedure has been delayed. 14 They reported a 100% secondary patency rate found on follow-up CTA, without any cases of permanent dialysis postoperatively. 14 The mean renal ischemic time to revascularization was 24 hours (range, 7-168 hours).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…They found that renal function can be salvaged, even if the revascularization procedure has been delayed. 14 They reported a 100% secondary patency rate found on follow-up CTA, without any cases of permanent dialysis postoperatively. 14 The mean renal ischemic time to revascularization was 24 hours (range, 7-168 hours).…”
Section: Discussionmentioning
confidence: 97%
“…13 Another recent study specifically of RAO found an incidence of 3.3% at 11 months of follow-up. 14 However, although the incidence and magnitude of the complication has been reported with greater frequency, available, highquality data regarding the possible treatment options and outcomes are lacking. At present, only a few case reports and one case series have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heideman et al describe the potential renal collateral network and cases with reestablishing renal function after endovascular salvage in patients with renal ischemia > 6 hours, (ranging from 7 to 168 hours). 14 The potential collateral renal network includes the lumbar and intercostal arteries that can salvage partial and complete kidney function in a case of acute renal artery occlusion. 15 The present case supports the theory of a collateral network and the possibility to preserve renal function and avoid permanent dialysis even after extensive renal ischemia time.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular intervention such as thrombolysis after renal stent-graft occlusion is often used and can be helpful to remove thrombus and avoid the distal peripheral small renal emboli and additional kidney damage. 14 Patients with rapid renal deterioration can be treated with endovascular thrombectomy (e.g Angiojet, Boston Scientific, USA) and immediate flow restoration followed by thrombolysis to avoid further ischemic renal damage. 14 Open surgical repair with aorto/visceral-renal or iliac-renal bypass is possible, but in most cases, endovascular treatment should be considered the primary option if available.…”
Section: Discussionmentioning
confidence: 99%